Identifying constraints on Roma minority education provision in Romania - Patache, Laura; Ghencea, Flavia Lucia; Neguriță, Octav (Technium Social Sciences Journal, 2022)
The legislative principles that govern Romanian education, such as ensuring equal opportunities and social inclusion and focusing education on its beneficiaries, are tested by the real-life situation of Roma children and young people. The pandemic has put pressure on the educational system. The closure of schools from March 2020 and the forced transfer of teaching activities to an online format are increasing the problems faced by Roma children and young people, in many cases blocking their access to education due to technological constraints. Family support is essential for primary school students and particularly in the case of digital learning. Many Roma families are not interested in spending money on education, especially if, in addition, they are losing income that older children bring home. For educators, Dewey’s (1944) prediction has come true: ‘If we teach today’s students as we taught yesterday’s, we rob them of tomorrow’ (p.167). For Roma students, digital education means no education as teachers are unable to connect with them. In Romanian schools today, the curriculum contains a vast amount of information but is not correlated with students’ ability to understand the sheer volume of knowledge taught and the purpose it serves. According to the OECD Programme for International Student Assessment’s (PISA’s) 2018 results, 41% of Romanian students are functionally illiterate (Organisation for Economic Co-operation and Development [OECD], 2018). According to the results of a study based on an online questionnaire, which presupposes a degree of digital literacy, in 2020 32% of young people enrolled in pre-university education did not have exclusive individual access to a functional device (desktop, laptop, tablet); despite that online application supposed, also, that some of the family members have digital abilities. (Romanian Institute for Evaluation and Strategy [RIES], 2020) Through our study, we aim to reveal the series of current problems faced by the Roma ethnic group when attempting to access the educational system, presenting the perspectives of both educators and learners.